Massive hydrosalpinx with torsion in second trimester of pregnancy: a case report - Kulshrestha, Rupita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Acute abdominal pain in pregnancy can be due to obstetrical (preterm labour), gastrointestinal, urinary causes etc. Pregnancy with large adnexal masses are rare presentations. This is a case report about a woman presenting to emergency with 16 weeks and 5 days of gestation with acute pain abdomen. Diagnosis of coexisting huge adnexal mass was made with ultrasound. No response to conservative therapy forced us to do laparotomy which showed huge hydrosalpinx with 4 twists around its pedicle. This case report emphasizes the need to keep hydrosalpinx with torsion in a differential diagnosis for acute pain abdomen in second or third trimester, especially if pain is not relieved on conservative management.